NOWE TECHNOLOGIE W POSTĘPOWANIU SĄDOWOADMINISTRACYJNYM A KONSTYTUCYJNE PRAWO DO SĄDU - Trybka, Wiktor (Kwartalnik Prawa Publicznego, 2016)
The use of new technologies in the court and administrative proceeding can be analyse from the point of view of such values as: right to court, efficiency and simplicity of proceeding, functions of court and administrative proceeding. New technologies in the court and administrative proceeding can be used in two stages: initiation of proceeding and examination of the case. The Law of Proceedings Before Administrative Courts in compared with administrative, civil and criminal proceedings creates many barriers to the use of electronic means. These restrictions not only cause disservice in realization of the right to court but also have adversely affect in performance of administrative courts tasks. By analysing the provisions of the Act can be found a few regulation that allow the side of the proceeding use of the achievements of modern technology. It will change after the amendment to The Law on Proceedings Before Administrative Courts Act. On the main-thing of current legislation there is a discrepancy in jurisdiction on the use of an electronic signature in submit of complaint to the administrative court.